Synthesis of an Al(18)F radiofluorinated GLU-UREA-LYS(AHX)-HBED-CC PSMA ligand in an automated synthesis platform - Giglio, Javier (EJNMMI Radiopharm Chem, 2018)
BACKGROUND: Overexpression of prostatic membrane antigen (PSMA) is associated with the progression and prognosis of prostate cancer. There are numerous studies using this peptide with the (68)Ga radionuclide. Previous methods to synthetize (18)F–labeled PSMA ligands with complexes [(18)F]AlF(2+) have been achieved. However, these reported syntheses were performed manually, using small volumes. Therefore it is only possible to have the radiopharmaceutical on a small scale, for use in preclinical studies. (18)F–labelled tracers allow higher doses increasing the number of examined patients. In addition, late images can be acquired in the case of uptake in lymph nodes, to discard inflammation. It is important to transfer the manual synthesis to an automatic module, producing a batch of the radiopharmaceutical with high activity in a safe and effective way. The aim of this work was to optimize the labeling of [(18)F]AlF-[GLU-UREA-LYS(AHX)-HBED-CC] in a Tracerlab FXFN® (GE) platform. RESULTS: The labeling up to the reactor corroborates the formation of the complex [(18)F]AlF-PSMA. After purification by HPLC, the radiopharmaceutical was achieved with a radiochemical purity higher than 90%. The quality control of the final product fulfilled all the requirements in agreement with USP, such as radiochemical purity (greater than 90%) and residual solvents. [(18)F]AlF-PSMA was obtained with a yield of 18 ± 3% (n = 7), not decay corrected (NCD) starting off from 500 to 2000 mCi the 18F and with a radiochemical purity of 95 ± 3% (n = 7). The product verified stability in the final formulation vial during 4 hs and in human plasma up to 1 h. CONCLUSION: The proposed method allowed the production of [(18)F]AlF-PSMA with suitable radiochemical purity in a commercial platform. High activities were achieved, with a simple and robust methodology appropriate for clinical purposes.